A 5.8 GHz Energy Harvesting Tag for Sensing Applications in Space - Qi, Cheng; Frederick, Quentin; Davis, Kaleb; Lindsay, Dakota; Cox, Julie; Parke, Stephen; Griffin, Joshua D.; Durgin, Gregory D. (2018 6th IEEE International Conference on Wireless for Space and Extreme Environments (WiSEE), 2018)
Passive backscatter radio frequency (RF) tags that harvest energy from an incident electromagnetic wave have found many terrestrial applications ranging from radio frequency identification (RFID) of parcels to motion detection systems. Such RF tags also have many potential applications for sensing in space such as monitoring spacecraft structural health or making sensitive electromagnetic field measurements. This paper presents a 5.8 GHz, energy-harvesting backscatter RF tag that contains temperature, total-dose radiation, and acceleration sensors. The tag will be launched into low-earth orbit aboard the Radio Frequency Tag Satellite (RFTSat), a nanosatellite developed by undergraduate students at Northwest Nazarene University, and serve as a demonstration of backscatter sensing in space. The tag can harvest energy when the incident power is greater than −2 dBm storing the energy in a supercapacitor controlled by a power management circuit. The supercapacitor can supply between 1.8 VDC and 3 VDC for an on-board microcontroller, sensors, and backscatter wireless communication.